1998
DOI: 10.1111/j.1151-2916.1998.tb02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relationships and Physical Properties of Homologous Compounds in the Zinc Oxide‐Indium Oxide System

Abstract: Equilibrium phase relationships in the ZnO-In 2 O 3 system were determined between 1100°and 1400°C using solidstate reaction techniques and X-ray diffractometry. In addition to ZnO and In 2 O 3 , nine homologous compounds, Zn k In 2 O k+3 (where k = 3, 4, 5, 6, 7, 9, 11, 13, and 15), were observed. Electrical conductivity and diffuse reflectance of the k = 3, 4, 5, 7 and 11 members were measured before and after annealing at 400°C for 1 h under forming gas (4% H 2 -96% N 2 ). Room-temperature conductivity incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
164
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(184 citation statements)
references
References 15 publications
17
164
1
Order By: Relevance
“…1 (JC PDF 00-020-1441) homologous phases were clearly detected, while the XRD pattern also indicates the possible formation of the phases for k ≥ 11 towards the pure ZnO phase, which could be identified in accordance with the report of Moriga et al [15] They also reported that only (ZnO) 5 (Fig. 2), with the largest having a length up to 5m and a thickness of approximately 0.8m.…”
Section: Resultssupporting
confidence: 90%
“…1 (JC PDF 00-020-1441) homologous phases were clearly detected, while the XRD pattern also indicates the possible formation of the phases for k ≥ 11 towards the pure ZnO phase, which could be identified in accordance with the report of Moriga et al [15] They also reported that only (ZnO) 5 (Fig. 2), with the largest having a length up to 5m and a thickness of approximately 0.8m.…”
Section: Resultssupporting
confidence: 90%
“…19 With further increases in solute concentration, individual InO 2 sheets form on the basal plane of ZnO and their spacing decreases until, at x ¼ 0.22 (k ¼ 7), a distinct, identifiable crystallographic compound Zn 7 In 2 O 10 forms. 18 So, in essence, a two-phase solid-solution region exists between pure ZnO and Zn 7 In 2 O 10 that according to the phase diagram persists up to 1175 C. (Above this temperature, a different superlattice spacing between the InO 2 sheets becomes stable. 18 ) While there remains some uncertainty as to the precise atomic arrangement in this compound, it is known to be rhombohedral (space group R3m ) and the InO 2 sheets are spaced 2.45 nm apart.…”
mentioning
confidence: 99%
“…18 So, in essence, a two-phase solid-solution region exists between pure ZnO and Zn 7 In 2 O 10 that according to the phase diagram persists up to 1175 C. (Above this temperature, a different superlattice spacing between the InO 2 sheets becomes stable. 18 ) While there remains some uncertainty as to the precise atomic arrangement in this compound, it is known to be rhombohedral (space group R3m ) and the InO 2 sheets are spaced 2.45 nm apart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the low Seebeck coefficient, the maximum value of PF is only 0.85 mW/m·K 2 at 330 K. Approximately the same thermoelectric parameters were obtained for sintered ZnO ceramics doped with indium [113][114][115][116][117][118][119]. When the concentration of In 2 O 3 in ZnO was increased to 10 mol%, the thermal conductivity of ZnO:In decreased to~1.6-2.0 W/m·K, and the ZT in samples with optimal doping reached values of~0.1 at 1073 K. According to [109,116], the optimization of the thermoelectric parameters of metal oxides from the ZnO-In 2 O 3 and ZnO-Ga 2 O 3 systems is conditioned by the specificity of point defects [120][121][122], generated at low doping levels, and by the formation of Ga 2 O 3 (ZnO) m and In 2 O 3 (ZnO) m superlattice compounds in the Ga and In highly doped ZnO. Such superlattices belongs to the RMO 3 (ZnO) m type of homologous layered oxides [111,119,[121][122][123].…”
Section: Nanostructuringmentioning
confidence: 99%